Construction of ZnS/Sb2S3 Heterojunction as an Ion‐Transport Booster toward High‐Performance Sodium Storage. (26th December 2022) - Dong, Caifu; Shao, Hengjia; Zhou, Yanli; Du, Wei; Li, Lin; Sun, Jianchao; Yan, Zhenhua; Hu, Zhe; Chou, Shulei; Jiang, Fuyi
Abstract: Metal sulfides have shown great promise for sodium‐ion batteries due to their excellent redox reversibility and relatively high capacity. However, metal sulfides generally suffer from sluggish charge transport and serious volume change during the charge–discharge process. Herein, potato chip‐like nitrogen‐doped carbon‐coated ZnS/Sb2 S3 heterojunction (ZnS/Sb2 S3 @NC) is precisely synthesized through a sulfurization reaction, and a subsequent metal cation exchange process between Zn 2+ and Sb 3+ . The theoretical calculations and experimental studies reveal the boosted charge transfer in ZnS/Sb2 S3 @NC composites. Therefore, the ZnS/Sb2 S3 @NC electrode exhibits excellent cycling stability (a high reversible capacity of 511.4 mAh g ‐1 after 450 cycles) and superior rate performance (400.4 mAh g ‐1 at 10 A g ‐1 ). In addition, ZnS/Sb2 S3 @NC is based on a conversion‐alloy reaction mechanism to store Na +, which is disclosed by the X‐ray diffraction and high resolution transmission electron microscopy analysis. This effective synthesis method can provide a reference for the design of other high‐performance electrode materials for sodium‐ion batteries. Abstract : Herein, ZnS/Sb2 S3 @NC composites are successfully prepared by introducing Sb2 S3 into ZnS via a facile cation exchange method. The ZnS/Sb2 S3 @NC composite exhibits superior cycling stability and rate performance due to its boosted charge transfer.